Association of whole blood heavy metal concentrations with kidney function - Zuo, Jiao; Huesker, Katrin; Liu, Yvonne; Hocher, Johann-Georg; Zhang, Xiaoli; von Baehr, Volker; Krämer, Bernhard; Hocher, Berthold (Scientific reports, 2025)
Relatively elevated concentrations of arsenic, lead, and mercury are toxic to the kidneys. However, it is unknown whether kidney function is influenced by these metals in the general population without kidney diseases and without known exposure to these metals. We did a retrospective analysis of data collected from 58,864 outpatients in Germany from January 2014 to October 2022 undergoing measurements of arsenic, lead, and mercury. Routine clinical laboratory parameters were entered into the database if they were analyzed in the same patient within +/- four weeks of the metal analysis. The estimated glomerular filter rate (eGFR) was calculated using the 2021 CKD-EPI equation. The mean age of the study participants was 50.3 ± 17.1, of which 61.8% were women. Complete blood count, CRP, fasting glucose, liver and lipid values, and thyroid function parameters were within the normal range. Median (IQR) eGFR level was 92.14 (79.44-103.85) mL/min/1.73m2. Median (IQR) whole blood values for arsenic were 0.8 (0.4-1.5) µg/l, median (IQR) level for lead was 13.6 (9.5-19.5) µg/l, median (IQR) values for mercury were 0.8 (0.3-1.5) µg/l in whole blood. Arsenic (r= -0.131, p < 0.001, N = 11,211), lead (r = 0.318, p < 0.001, N = 21,733), and mercury (r= -0.149, p < 0.001, N = 22,670) levels correlate all inversely with eGFR. When plotting eGFR against whole blood metal concentrations, no lower safety thresholds were found. Multivariate analysis, considering age, sex, CRP, and fasting glucose as confounding factors, confirmed findings of independent associations of arsenic, lead, and mercury on eGFR. Subgroup analysis revealed that this inverse relationship was particularly pronounced in the lowest age tertile of all study participants. Concentrations of arsenic, lead, and mercury correlated independently inversely with eGFR in a German cohort that largely had a normal kidney function with no known exposure to heavy metals.